Legal Protection For Minors Who Are Victims Of Human Trafficking - Gusnarib, Gusnarib; Adawiyah, Siti Rabiatul (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2023)
Human trafficking is a transnational crime that can be said to be rampant and is a form of violence against children and women, even a criminal act that is aften committed across national borders. The criminal act of human trafficking is a number of things that are the driving factors are the economy which is below the poverty line, family, environment, and ,education, especially children and women who are most vulnerable. This form of legal protection for children as victims of criminal acts of human trafficking provides legal assistance to children with the aim of protecting children’s right as victims of human trafficking can be fulfilled in the criminal justice process by demanding compensation rights that can be seen from the humanitarian aspect and the child’s human rights. The Indonesia government has also made efforts to prevent and overcome the problem of human trafficking in several ways, such as the establishment of law number 23 of 2002 concerning amendemen to law number 35 of 2014 concerning child protection, as well as law number 21 of 2007 concerning human trafficking.